Digital (Electronic) Democracy in Russia: Issues of Further Development - Lolaeva, Albina; Lebedeva, Margarita; Matveeva, Natalya; Nesmeianova, Irina; Ocheredko, Victor; Platonova, Svetlana (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
The study addresses the issues of further development of digital (electronic) democracy in Russia. Digitalization has penetrated all spheres of public life. The sphere of public administration is no exception. The authors provide various scientific interpretations of democracy as a form of exercise of state power, in which the individual is given maximum freedom to exercise their rights and freedoms and the ability to participate in the state's public life. The study employs general scientific and private scientific methods. The authors conclude that developing information and communication technologies will completely reorganise public administration systems. The advancement of scientific and technological progress makes it possible to implement the power of the people in various digital (electronic) forms. The construction of an electronic state is in full swing. To develop a highly advanced, sovereign, prosperous state, it is necessary to safely introduce the tools of digital (electronic) democracy into the country's political life.